Grid-tied hybrid energy storage system based on modular multilevel converter - Ding, Jinde (2017)
The intermittency and variability of renewable energy hinder further development in large scale commercial applications. To efficiently utilize the renewable energy, energy storage system is an attractive option to connect the renewable energy source to the grid directly. However, a conventional battery energy storage system is inefficient to handle high frequency power. A hybrid energy storage system based on Modular Multilevel Converter (MMC) is proposed to solve this problem. Compared with conventional two level converters, MMC has the advantage of less passive devices, high voltage conversion accuracy and lower power losses. Hence, MMC has gradually become a popular choice in high power applications. A combination of battery and supercapacitor can be effectively exploited to deal with the power fluctuation as voltage regulation required, which can increase the flexibility, improve the efficiency and prolong energy storage system lifespan. The battery has high energy density and low power density, capable of handling low frequency power effectively. The supercapacitor has high power density and low energy density, capable of coping with high frequency power effectively. An existing topology is proposed and proved in this project. Battery is implemented on the upper arm and supercapacitor is implemented on the lower arm. This topology is capable of distributing power suitably according to power requirement with a specifically designed power decoupling. The MMC operational theory are introduced in this report. Based on these analysis, a fully designed control scheme can optimize the performance of system and realize the required functions, such as power decoupling and supercapacitor voltage control. Power decoupling is the most significant component to effectively utilize the structure of battery-supercapacitor combination. The power fluctuation from power resource is compatibly split into two parts for battery and supercapacitor. Active power and reactive power control determines the power provided/absorbed by grid. The SOC control and the supercapacitor control are two significant technologies to balance the statue of battery and supercapacitor, which makes sure these energy units works in identical state among phases and submodules. Different from MMC acting as AC/DC voltage converter, the circulating current in MMC-HESS should not be suppressed to 0. Circulating current control can manipulate the circulating current to help power decoupling on upper arm and lower arm. In this project, a proposed MMC-HESS model based on MATLAB/Simulink is constructed for simulation. All these control strategies are realized and verified on this model. This model has been proven to be feasible and credible.